PENYELESAIAN SENGKETA PERCERAIAN MELALUI MEDIASI OLEH PENGADILAN DI PENGADILAN AGAMA PEKANBARU - Aulia, Rizqah Zikrillah; Lestari, Rika; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Divorce is happening in conjugal is not just things that are material, but solely due to hit the needs and attitudes everyday from each party that wants to win themselves. The divorce hamper efforts applied by asserting that divorce can only be done in front of the court. the religious courts, at the first hearing the judge will advise the parties to the mediation must be carried out and included in the minutes of the hearing. The purpose of this skripsi, namely First, the mechanism of dispute settlement through mediation by the court divorce in religious courts Pekanbaru, both the effectiveness of the implementation of problem divorce settlement through mediation in the religious court Pekanbaru, third, efforts to implement a divorce dispute settlement through mediation to be effective in the religious court Pekanbaru. Keywords : Dispute Resolution - Divorce - Mediaton